2020
DOI: 10.9755/ejfa.2019.v31.i12.2043
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive constituents of red and green lettuce grown under colour shade nets

Abstract: The objectives of this study were to investigate the effects of coloured shade-nets (pearl, blue, or red all with a 50% shade index) compared to non-shaded plants on quality traits on the Discoa and ICE 40102 (green-leaf) and Eglantine (red-leaf) lettuce cultivars. Total chlorophyll content depended on the shading and lettuce genotype. The chlorophyll a and b contents were higher in shaded than unshaded plants. The cv. Eglantine had the highest total chlorophylls (637.03 μg∙g-1 F.M.) content. The highest carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
(37 reference statements)
2
4
0
1
Order By: Relevance
“…Among colored shade nets, pearl had the greatest DLI for both seasons. The greater DLI for pearl shade nets is consistent with the manufacturer descriptions, which indicate a design to minimize the absorption of visible light and instead transmit direct radiation into diffuse or scattered light (Ilic et al 2019;Shahak et al 2008). Gaurav (2014) also found that pearl shade net had the greatest light intensity compared with red and black shade nets.…”
Section: Discussionsupporting
confidence: 60%
“…Among colored shade nets, pearl had the greatest DLI for both seasons. The greater DLI for pearl shade nets is consistent with the manufacturer descriptions, which indicate a design to minimize the absorption of visible light and instead transmit direct radiation into diffuse or scattered light (Ilic et al 2019;Shahak et al 2008). Gaurav (2014) also found that pearl shade net had the greatest light intensity compared with red and black shade nets.…”
Section: Discussionsupporting
confidence: 60%
“…One of the reasons for the lack of correlation between flavonoids and EC 50 value can be attributed to secondary metabolites that could not be detected in this study, such as antioxidant vitamins (vit C and E), carotenoids, quercetin, tannins, etc. [29]. Higher content of total phenol compounds resulted in higher antioxidant activity indicating a higher correlation for TP content (R 2 = 0.774) (Figure 2).…”
Section: Total Antioxidant Capacity (Tac)mentioning
confidence: 94%
“…The content of total phenols was determined in herb extracts by the Folin-Ciocalteu procedure [25][26][27][28][29] using gallic acid as a standard (the concentration range 0.00625 to 0.2 mg/mL). The results are expressed as gallic acid equivalents per gram of dry extract (mg GAE g −1 d.e.…”
Section: Determination Of Content Of Total Phenols In Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Koristi se gotovo cijele godine zbog postojanja varijeteta koji se mogu uspješno proizvoditi tijekom različitih sezona (Zdravković et al, 2014). Posljednjih godina povrćari su usavršili tehnologiju ljetne proizvodnje salate uz primjenu fotoselektivnih mreža (Ilić et al, 2019).…”
Section: Uvodunclassified